1986
DOI: 10.1073/pnas.83.3.556
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of bases 787-795 of Escherichia coli 16S ribosomal RNA in ribosomal subunit association.

Abstract: The functional involvement of rRNA in the protein translation cycle is becoming increasingly apparent (1). Already well documented is the role rRNA plays in mRNA initiation (2) and tRNA binding (3)(4)(5)(6). In addition, some rRNA sites have been implicated in the peptidyltransferase center (7), and subunit-subunit interactions (8-10).Exposed regions of the rRNA have been probed using chemical modification and nuclease digestion techniques. Examples include guanine-specific kethoxal (11), adeninespecific dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 24 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…The 23 S rRNA and DNA were incubated on ice for ®ve minutes and then at 42 C for ®ve minutes. Next, the volume was adjusted such that the ®nal RNA concentration was approximately 1 mM, and the salts adjusted to 40 mM Tris (pH 7.9), 10 mM MgCl 2 , 60 mM KCl, and 1 mM DTT (Tapprich & Hill, 1986). Cleavage was initiated by the addition of 0.02 units of RNase H/ml reaction (Wako Pharmaceuticals) and allowed to proceed for 20 minutes at 42 C. Reaction was stopped by extracting with neutralized phenol, and precipitating with two volumes of ethanol.…”
mentioning
confidence: 99%
“…The 23 S rRNA and DNA were incubated on ice for ®ve minutes and then at 42 C for ®ve minutes. Next, the volume was adjusted such that the ®nal RNA concentration was approximately 1 mM, and the salts adjusted to 40 mM Tris (pH 7.9), 10 mM MgCl 2 , 60 mM KCl, and 1 mM DTT (Tapprich & Hill, 1986). Cleavage was initiated by the addition of 0.02 units of RNase H/ml reaction (Wako Pharmaceuticals) and allowed to proceed for 20 minutes at 42 C. Reaction was stopped by extracting with neutralized phenol, and precipitating with two volumes of ethanol.…”
mentioning
confidence: 99%
“…The site chosen in the present experiment is U788 in the 790 loop of the 16S rRNA+ This region is present in all small subunit RNAs and is highly conserved in sequence+ It has been implicated in several important 30S functions including subunit association (Chapman & Noller, 1977;Herr et al+, 1979;Santer et al+, 1990), IF3 binding (Muralikrishna & Wickstrom, 1989;Moazed et al+, 1995;Tapprich & Hill, 1986;Tapprich et al+, 1989), and tRNA binding (Moazed & Noller, 1990)+ The physical location for the region in the subunit has been investigated by DNA hybridization electron microscopy and was proposed to be in the end of the 30S subunit platform structure (Oakes & Lake, 1990); however, there is a significant distance between the decoding region and the proposed site, and it has been difficult to reconcile the rRNA segment location with its function+ The crosslinks made by the site-specific psoralen (SSP) reagent in these experiments are with a number of RNA sites that must be in the central part of the 30S subunit and this indicates a location for the nucleotides U788/U789 in the central part of the subunit much closer to the decoding region than previously thought+…”
mentioning
confidence: 99%
“…We must also take into account the actual position of the 59-thiophosphate group relative to the rRNA to which the probe is bound+ If we look at the 59 end of the probe-rRNA complex, we can see that the thiophosphate group (and the attached phenanthroline) may take one of eleven possible positions "around the clock" (see Fig+ 7A)+ It cannot be known, a priori, in which position the thiophosphate group actually resides+ We do know that all of the cleavages have emanated from the thiophosphate positioned at only one of the eleven positions+ It has been suggested that hybridizing a complementary DNA oligomer to the ribosomal RNA may create a significant structural deformation in the RNA+ This is difficult to test+ Although previous work in this lab has shown that poly(U)-directed poly-phe synthesis in the presence of the 790-probe was maintained at 84% of control (Tapprich & Hill, 1986), there is no evidence that the 790 probe remains annealed to the target+ This would be unlikely, since the 790 loop has been shown be involved in subunit association (Herr et al+, 1979;Tapprich & Hill, 1986; Merryman et al+, 1999)+ Successful tRNA binding experiments in the presence and absence of probe would prove little, because the protected nucleotides in the 790 loop have been reported to be nonessential for effective tRNA binding (von Ahsen & Noller, 1995)+ The presence of the probe did not alter poly U directed tRNA Phe binding nor was the probe dissociated from FIGURE 7. Molecular model of the possible orientations of the tethered phenanthroline about the 59 end of the A-form helix composed of the DNA-rRNA hybrid+ The phosphate atoms are depicted as orange spheres with attached red oxygen atoms+ A: 20-Å diameter helix formed by binding the oP-DNA to the rRNA as viewed down the 59 end of the helical axis+ In addition to the phenanthroline (boxed in yellow in both panels) being in one of eleven possible orientations about the helical axis, the phenanthroline can rotate about the methylene carbon to produce a multitude of orientations capable of sweeping out to adjacent structures to produce unique cleavage events+ B: Helical view with the RNA phosphate backbone in the foreground illustrating the proximity of the tethered phenanthroline to both the 59 and 39 ends of the RNA+ the 30S subunit upon tRNAP he binding as determined by a dual-label filter binding assay (data not shown)+ Conducting free phenanthroline cleavage in the presence and absence of probe will provide some additional information on possible structural deformation due to the probe+ If significant structural deformation were to occur in the presence of the probe, additional phenanthroline cleavage sites should appear, if the deformation is accompanied by the formation of strained regions of RNA+ Phenanthroline, which shows a preference for cleaving strained regions of RNA (Muth & Hill, 1999), should cleave the strained RNA in control reactions containing free phenanthroline and the complementary probe+ No such probe induced free phenanthroline cleavages were observed when compared to free phenanthroline cleavages (data not shown) throughout the entire 16S rRNA+ A final estimation concerning the minimal structural distortion caused by the probe lies in the 693 cleavage itself+ An accepted distance between nt 794 and 693 has been reported to be 11 6 4 Å (Malhotra & Harvey, 1994)+ Our equivalent distance suggests that if a structural change is occurring because of the probe, it is not affecting this distance+…”
Section: Discussionmentioning
confidence: 67%
“…The proximity of the 582-584 region to the 790 region has not been previously reported+ Although the central domain of 16S rRNA has been well localized in the model published by Malhotra & Harvey (1994), parts of helix 20 (nt 581-587) have a reported standard deviation of 15 Å due to the lack of structural data available+ The results presented here will allow the placement of helix 20 with greater certainty than previously reported+ Two conditions are needed for effective directed phenanthroline cleavage of ribosomal subunits+ The first condition involves using a suitable oligomeric probe to direct phenanthroline to regions within the ribosome+ DNA oligonucleotides have been extensively used to probe the availability of certain sites within the ribosome (Tapprich & Hill, 1986;Hill et al+, 1988Hill et al+, , 1990bWeller & Hill, 1991)+ Probes complementary to the 790 region, specifically complementary to nt 787-795, previously showed binding at 38% efficiency when used at a 10:1 ratio of probe to 30S ribosomal subunits (Tapprich & Hill, 1986)+ A short DNA oligomer complementary to this region, complexed with two phenanthroline reagents IoP and BHoP (ee Fig+ 1), was used in this study+…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation